Analisis Perhitungan Harga Pokok Penjualan Dan Penentuan Harga Jual Produk Menggunkan Metode Cost Plus Pricing (Studi Kasus Pada Usah Home Industri Bahan Bangunan Pilar Jaya Di Sukadana Lampung Timur) - Ambarwati, Retno; Nusantoro, Jawoto; Septiani, Ana (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to analyze the calculation of cost of goods sold and determination of product selling prices using the cost plus pricing method in the Pilar Jaya building materials home industry business in Sukadana, East Lampung. This research uses a descriptive method with a qualitative approach. The results showed that there were differences in the results of the analysis of the calculation of cost of goods sold using the activity-based costing method and the determination of selling prices using the cost plus pricing method with the calculation of cost of goods sold and determining selling prices according to the company. Based on the results of the analysis and calculations that have been carried out, it can be concluded that the calculation of cost of goods sold using the activity-based costing method in the Pilar Jaya home industry obtained a result of Rp 57,283,362.97. This result is lower than the calculation of cost of goods sold according to the company. While the calculation of determining the selling price using the cost plus pricing method in the Pilar Jaya home industry obtained a pilar price of IDR 296,305, a lisplang price of IDR 144,956, a roster price of IDR 11,057, and a buis beton price of IDR 145,087. The selling price using the cost plus pricing method is lower than the selling price according to the company.